2015
DOI: 10.1111/tbed.12319
|View full text |Cite
|
Sign up to set email alerts
|

Financial Impacts of Foot-and-Mouth Disease at Village and National Levels in Lao PDR

Abstract: To assist policies on Foot-and-Mouth Disease (FMD) control in Laos and the Mekong region, the financial impact of recent outbreaks at village and national levels was examined. Village-level impacts were derived from recent research on financial losses due to FMD per smallholder household and number of households with FMD-affected livestock in the village. National-level impacts of FMD were determined from examination of 2011-2013 FMD reported to the Lao Department of Livestock and Fisheries (DLF), with the 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Similar studies on the benefits of vaccination against other diseases including FMD in Laos (Nampanya et al . ) and HS in Cambodia (Kawasaki et al . ) confirm that routine vaccination for priority large ruminant diseases is a cost‐effective disease management strategy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies on the benefits of vaccination against other diseases including FMD in Laos (Nampanya et al . ) and HS in Cambodia (Kawasaki et al . ) confirm that routine vaccination for priority large ruminant diseases is a cost‐effective disease management strategy.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the cost of FMD in Laos indicated that each dollar invested potentially achieved USD 5 in benefits (Nampanya et al . ), with net benefits at the smallholder farmer level of USD 22 for cattle and USD 33 for buffalo, following biannual FMD vaccination (Nampanya et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…PPR virions are excreted for 10 days post onset of fever: hence incidence studies require quick sampling of suspect animals (Parida et al., ). This is achievable as demonstrated through widespread knowledge of FMD virus throughout the country (Nampanya et al., ). Improving the capacity of regional laboratories will be beneficial for a more rapid diagnosis and potentially disease management response to a PPRV outbreak, plus increased diagnostic abilities for additional livestock diseases. Political and financial support.…”
Section: Discussionmentioning
confidence: 99%
“…Foot‐and‐mouth disease (FMD) is a highly contagious viral disease affecting cloven‐hoofed domestic and wild animals. It is endemic in mainland South‐East Asia (SEA) comprising Cambodia, Lao People's Democratic Republic, Peninsular Malaysia, Myanmar, Thailand and Vietnam, and poses a significant burden to the agriculture sector owing to loss of animal production and access to international markets (Nampanya et al., ). Control of FMD in the region is constrained by gaps in disease surveillance and reporting, substantial unregulated livestock movements, and insufficient vaccination coverage (OIE‐SEACFMD, ).…”
Section: Introductionmentioning
confidence: 99%